2017
DOI: 10.1155/2017/5713249
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between IGF-I Concentration and Metabolic Profile in Children with Growth Hormone Deficiency: The Influence of Children’s Nutritional State as well as the Ghrelin, Leptin, Adiponectin, and Resistin Serum Concentrations

Abstract: Background Some, however not all, children with growth hormone deficiency (GHD) reveal a tendency towards metabolic disorders. Insulin-like growth factor I (IGF-I) is the main mediator of GH anabolic effects. Objective The aim of the study was to compare ghrelin, adiponectin, leptin, resistin, lipid, glucose, and insulin concentrations in GHD children, depending on the IGF-I bioavailability. Methods The analysis comprised 26 children with GHD, aged 5.7–15.3 yrs. Fasting serum concentrations of IGF-I, IGFBP-3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 48 publications
3
20
0
Order By: Relevance
“…Concerning the present results of BMI,they are similar to those of other studies [24,25] which reported non-significant differences in BMI between the GH deficient patients and the control group,while theyare indisagreement with other reports [29] . The reason might be that BMI depends on the weight and height and thatit is not clear whether there is a similar association between BMI and peak GH level in healthy children [24].…”
Section: Anthropometric Measurements Of Ghdeficient Patients and The supporting
confidence: 92%
“…Concerning the present results of BMI,they are similar to those of other studies [24,25] which reported non-significant differences in BMI between the GH deficient patients and the control group,while theyare indisagreement with other reports [29] . The reason might be that BMI depends on the weight and height and thatit is not clear whether there is a similar association between BMI and peak GH level in healthy children [24].…”
Section: Anthropometric Measurements Of Ghdeficient Patients and The supporting
confidence: 92%
“…Its endocrine function could be partially modulated by the GH/ IGF-1 axis and adipokines derived from adipose tissue possibly mediate some metabolic actions of GH, such as the influence on energy balance and glucose and lipid metabolism (Kershaw et al, 2004;Trayhurn et al, 2006;Berryman et al, 2011;Meazza et al, 2014;Ciresi et al, 2016;Rothermel et al, 2016;Berryman et al, 2017). Several studies indicate that in patients with GHD, both children and adults, the adipokine profile could be impaired, and GH replacement therapy could be beneficial, but the reported results are discordant (Ciresi et al, 2007;Nozue et al, 2007;Andersson et al, 2009;Ciresi et al, 2016;Oświęcimska et al, 2017;Stawerska et al, 2017). Concentrations of adiponectin seem to be unaffected in children with untreated GHD (Ciresi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Resistin concentrations in untreated GH-deficient children are usually higher than in healthy controls, but the effects of GH treatment on resistin concentrations are divergent (Nozue et al, 2007;Meazza et al, 2014;Ciresi et al, 2016;Stawerska et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations